2009 10th International Conference on Document Analysis and Recognition 2009
DOI: 10.1109/icdar.2009.163
|View full text |Cite
|
Sign up to set email alerts
|

CASIA-OLHWDB1: A Database of Online Handwritten Chinese Characters

Abstract: This paper describes a publicly available database, CASIA-OLHWDB1, for research on online handwritten Chinese character recognition. This database is the first of our series of online/offline handwritten characters and texts, collected using Anoto pen on paper. It contains unconstrained handwritten characters of 4,037 categories (3,866 Chinese characters and 171 symbols) produced by 420 persons, and 1,694,741 samples in total. It can be used for design and evaluation of character recognition algorithms and cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…In order to assess character segmentation algorithms, a database of touching Chinese characters was compiled from the CASIA handwriting database [187,188]. This database was termed as CASIA-HWDB-T [194].…”
Section: Touching Character Databasementioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess character segmentation algorithms, a database of touching Chinese characters was compiled from the CASIA handwriting database [187,188]. This database was termed as CASIA-HWDB-T [194].…”
Section: Touching Character Databasementioning
confidence: 99%
“…CASIA [187,188] is a widely used Chinese handwritten database comprising handwritten paragraphs as well as isolated characters The data was collected from 1020 individuals who produced writings on paper with a digital pen. This allowed capturing the online trajectory information as well as the offline images of text.…”
Section: Casia: Online and Offline Chinese Handwriting Databasesmentioning
confidence: 99%
“…For online version of OR3C dataset, we use a stateof-the-art recognizer [9] [10], the experimental setting is similar with [6]. First, we reduce the dimension of images to 64×64, normalize all the images with pseudo 2D moment normalization method.…”
Section: A Experiments With Online Datasetmentioning
confidence: 99%
“…The unconstrained character recognition remains one of the most challenging tasks [5]. One of the most critical bottlenecks for improving its recognition performance is the short of available large-scale unconstrained handwriting dataset [6].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by these, many researchers devoted themselves to the field of handwriting character recognition and achieved great progress during the past 40 years [1][2][3]. However, recent researches [4][5][6] have shown that the recognition accuracy using state-of-the-art techniques cannot satisfy user's expectations [7].…”
Section: Introductionmentioning
confidence: 99%